Clinical Approaches to Nestorone Subdermal Implant Therapy in Women’s Health - Guilherme Renke; Consuelo Callizo; Raphaela Paes; Mariana Antunes; Glaycon Michels; Luana Concha; Ordânio Almeida; Christiane Valente; Thomaz Baesso; Bruna Giovannoni (Biomedicines, 2023)
Segesterone acetate (SA) or Nestorone, a fourth-generation progestogen, is a synthetic compound with high progestational activity and no androgenic, glucocorticoid, or anabolic effects. However, due to its oral inactivity, SA must be used by other routes, such as subcutaneous. Thus, considering its peculiar properties, the SA subdermal implant is successfully used in female contraception and postmenopausal hormone replacement therapy (HRT). In recent years, its potential uses in endometriosis, polycystic ovaries syndrome (PCOS), and a new therapeutic possibility for neuroprotection have made this treatment extremely interesting. However, the absence of a standardized dose and the long-term safety of SA implant therapy in women is still controversial. Here, we present the possible indications, doses, limitations, and side effects of SA implant therapy.